Using the Guided Reading Strategy to Improve Students’ Reading Comprehension - Rahma, Nadia; Mashuri, Mashuri; Agussatriana, Agussatriana; Suriaman, Aminah (Journal of English Language and Education, 2025)
Reading comprehension is a fundamental skill in English learning, yet many students still face difficulties in understanding texts effectively. This gap between theory and classroom practice calls for more effective teaching strategies. This study aimed to examine the effectiveness of the Guided Reading Strategy (GRS) in improving the reading comprehension of eighth-grade students at SMP Negeri Model Terpadu Madani. Using a quasi-experimental design, the research involved an experimental and a control group. Data were obtained through pre-tests and post-tests and analyzed using SPSS version 27 with Levene’s Test, Shapiro–Wilk Test, and the Mann–Whitney U Test. The findings revealed that the mean post-test score of the experimental group (78.31) was approximately 20% higher than that of the control group (65.06), indicating a significant improvement in students’ reading comprehension. Therefore, the Guided Reading Strategy effectively enhanced students’ ability to comprehend definition exposition texts.